Exploring Frontline Police Responses To, and Interactions With, Māori Experiencing Mental Distress in South Auckland, Aotearoa New Zealand - Hunter, Kiri (Auckland University of Technology, 2024)
Emergency mental health demand in Aotearoa New Zealand currently stretches beyond the ‘ideal’ functions of frontline policing. Mental distress callouts range from welfare checks to mental health crises, with around-the-clock police responses occurring at the nexus of mental health, social, and criminal justice systems. This means that when frontline police work alongside mental health professionals, the practice boundaries that should ideally define their discrete functions become blurred. In recognition of the government’s accountabilities under the nation’s founding document, Te Tiriti o Waitangi, New Zealand Police value being culturally and equitably responsive to Indigenous Māori. However, social justice discourses endure as Māori health disparities persist. This study therefore informs an under-researched topic and strategic priority for both Māori and New Zealand Police. It explores frontline police responses to, and interactions with, Māori experiencing mental distress in South Auckland, or Counties Manukau Police District. With a critical kaupapa Māori lens informed by intersectionality, my study is complementary and sympathetic to Indigenous and Western theoretical perspectives. It relies on data generated from qualitative research methods conducted over two distinct phases. The whānau experience phase involves kaupapa Māori narrative inquiry with five participants from three different whānau interviewed during marae-based hui. The narratives are interpreted using a whakapapa and intersectionality framework. The police experience phase involves six months of ethnographic fieldwork, with ride-alongs and informal conversations with 32 frontline police conducted over 120 hours, and five semi-structured interviews. Through reflexive thematic analysis a richly contextualised and interpretative narrative of the police experience dataset is produced. The biphasic findings are then analysed as a complete, integrated data set, and responses to the study questions established. My findings emphasise the intersectional impact of multiple marginalised social positions for whānau Māori and the diversity of mental distress events. Frontline police played a key role in maintaining unwell, or otherwise mentally distressed whānau in the community, yet they also acted as agents of social exclusion and criminalisation when complex events led to more reactive and formalised pathways. Inherent to frontline policing are the concepts of power-holder legitimacy, coercion, and identity management yet, despite the perception that frontline police have considerable power, the reality is they often felt powerless to act in people's best interests. As default mental health providers police encountered mental health service access barriers, they managed complex cross-sector relations and occupied a liminal ‘waiting room’ space. They also received minimal mental health or Māori cultural responsiveness training. With no mechanisms for police to advocate for broader hauora Māori needs, biomedically centred public mental health services were instead viewed as the triage service that should lead the mental health and cultural needs of whānau. Frontline police worked to counter existing stereotypes around police bias and discrimination towards Māori, yet that mindset meant they treated all people equally. A state of stereotype paralysis existed which inhibited more equitable responses. Given the huge volume and repetition of the work by police dealing with mental distress events, it was made clear that failures in the mental health response, both clinically and culturally, must be urgently addressed. A cross-sector approach that recognises police’s place as a social service provider that protects the public, that considers the interactive effects of multiple minority status, and that promotes an equitable and holistic te ao Māori sociocultural model of health is required.